Heterotic patterns of 30 maize lines derived from CIMMYT's population 43 SR. - Terron, Arturo; Preciado, Ernesto; Córdova, Hugo; López, Raymundo (Agronomía Mesoamericana, 2016)
Observed 30 selected lines were crossed to two testers: CML-320 (heterotic group “A”) and CML- 321 (heterotic group “B”). The 60 line x tester combinations were evaluated at four location in the subtropical region of Mexico. In the combined analysis across locations the variance componentsfor the GCA and SCA were significant for grain yield. Significant SCA values allowed the separation of the inbred lines into two opposite heterotic groups based on the performance of the test crosses. On the basis of this information, two synthetics were formed with 7 inbred lines each defined as heterotic groups “A” and “B”. Nine single crosses outyielded the commercial check hybrid. Across locations the top yielder hybrid produced 9.48 t/ha which was 15.6% higher than the check. Average yield by location was 7.1, 3.8, 11.1 and 9.0 t/ha at Tlaltizapán, Tlajomulco, Celaya y Pabellón, respectively. Positive and significant GCA values were observed in six inbred lines. The GCA effects ranged from 1.18 to -2.19. The inbred lines from this study can effectively be used in hybridization programs.